وصف الناقة في معلقة طرفة بن العبد (مجلة جامعة سرت للعلوم الانسانية, 2022)
Description of the she-camel in the hanging of Tarfa bin Al-Abd, This research aims to know the relationship of the pre-Islamic poet with his camel, by describing it accurately, by drawing a great painting that carries all the colors in the desert (both inanimate and moving), to convey to the recipient that his camel is his savior when he realizes them. The pre-Islamic era was the subject of study by great and young writers alike, and its description was rich in natural materials, because the poet was provoking his intellectual, visual and auditory powers to surround his she-camel with all the qualities of greatness, strength and loftiness.He extracted his material from the desert, and borrowed from it what corresponded to his inclinations aimed at strength, bullying and vigor. Which indicates the accuracy of the poet's observation and his influence on what surrounds him in his community and environment
Keywords: Alnaga; Tarfa; Algahiela